80.5=7(m+3.6)

Simple and best practice solution for 80.5=7(m+3.6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 80.5=7(m+3.6) equation:


Simplifying
80.5 = 7(m + 3.6)

Reorder the terms:
80.5 = 7(3.6 + m)
80.5 = (3.6 * 7 + m * 7)
80.5 = (25.2 + 7m)

Solving
80.5 = 25.2 + 7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
80.5 + -7m = 25.2 + 7m + -7m

Combine like terms: 7m + -7m = 0
80.5 + -7m = 25.2 + 0
80.5 + -7m = 25.2

Add '-80.5' to each side of the equation.
80.5 + -80.5 + -7m = 25.2 + -80.5

Combine like terms: 80.5 + -80.5 = 0.0
0.0 + -7m = 25.2 + -80.5
-7m = 25.2 + -80.5

Combine like terms: 25.2 + -80.5 = -55.3
-7m = -55.3

Divide each side by '-7'.
m = 7.9

Simplifying
m = 7.9

See similar equations:

| 5+44x=53+8x | | 7=9x-7 | | 7z-7=5+32 | | b=4b | | 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 | | x-8.2=4.5 | | 9r-6r+6=6r+6-r | | -2w-4w-24=48 | | 736=4(x+18) | | 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 |

Equations solver categories